MODERN BIOMATERIALS AND BONE REGENERATION METHODS IN DENTAL IMPLANTATION - Khabibullayeva , Gulnora (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
This article provides a comprehensive and in-depth analysis of the latest scientific and clinical advances in modern biomaterials and bone regeneration methods used in dental implants for 2023–2026. The biocompatibility, osseointegration rate, mechanical strength, corrosion resistance, surface modifications, and interaction with peri-implant tissues of titanium alloys, zirconia, PEEK, and new composite materials are covered in detail. In bone regeneration, guided bone regeneration (GBR), 3D and 4D printed individual scaffolds, ion-enriched bioceramics (Sr, Mg, Ce doping), bioactive glass-polymer composites, hydrogels (GelMA, PEG, hyaluronic acid, chitosan-based) functionalized with stem cells (BMSCs, DPSCs, HERS), sustained and phased release of growth factors such as BMP-2, VEGF, SDF-1, exosome and miRNA enriched systems, immunomodulation (M2 macrophage polarization), angiogenesis and osteogenesis mechanisms are reviewed. The article combines laboratory studies, animal models (calvarial, mandibular, femoral defects), clinical cases, randomized trials, and current clinical trials (e.g., maxillary bone regeneration with PCL scaffolds) to evaluate the potential of biomaterials to accelerate bone tissue integration, reduce inflammation, reduce the risk of peri-implantitis, minimize marginal bone loss, and provide long-term (5–13 years) stability. The results suggest that 3D printing, biomimetic multiphasic designs, smart (stimulus-responsive) materials, and combined approaches can increase clinical success by 30–70%, but biodegradation rate control, lack of vascularization, immune responses, long-term mechanical stability, and translational hurdles (regulatory approval, scaling) need to be addressed.